CTNI-58. IMPROVING TRIAL ACCESS FOR PEOPLE WITH RARE CNS TUMORS: AN NCI-CONNECT PHASE I/II TRIAL OF PLX038 IN TUMORS WITH MYC/MYCN AMPLIFICATIONS INCORPORATING CORRELATIVE STUDIES AND PATIENT REPORTED OUTCOMES. (14th November 2022) - Penas-Prado, Marta; Wooley, Joseph; Jung, Jinkyu; Yuan, Ying; Zhang, Meili; Baranello, Laura; Briceno, Nicole; Levens, David; Mendoza, Tito; Pommier, Yves; Thomas, Craig; Vera, Elizabeth; et al.
Abstract: MYC genes encode transcription factors that regulate expression of genes involved in cell division. Supraphysiologic levels of MYC drive oncogenesis in many human cancers and induce the formation of topoisome complexes, essential to managing the torsional strain that would otherwise oppose transcription and replication. MYC/MYCN amplifications are seen in multiple primary CNS tumors including 30% of relapsed medulloblastomas (MB) and a subtype of ependymoma (EPN) where MYCN amplification defines the tumor. PLX038 is a PEGylated macromolecule containing the topoisomerase I inhibitor SN-38. PEGylations lead to longer half-life, tumor accumulation and decreased toxicity. We hypothesize that PLX038 will be efficacious in primary CNS tumors driven by MYC/MYCN amplifications by targeting the MYC -induced topoisome (Das, S.K. 2022 DOI10.1016/j.molcel.2021.11.016). METHODS: Trial in development. Design/Objectives: Phase I (N = 12) – determine the maximum tolerated dose and recommended phase 2 dose of PLX038 in recurrent primary CNS tumors using TITE-BOIN design. Phase II - 3 independent cohorts, N = 30 for each group with interim analysis after 10 each: 2A - MYC-N amplified EPN post resection and radiotherapy (PFS); 2B - Recurrent MYCN amplified EPN or MYC/MYCN amplified MB (disease control rate, DCR); 2C - Other recurrent primary CNS tumors with MYC/MYCN amplifications (DCR). Additional measures: PROs from the Office of Patient-Centered Outcomes Research (OpCORe) web-based early phase trial endpoints; biomarkers of PLX038 distribution and response/resistance in peripheral blood, tumor tissue, hair follicles, and abdominal wall fat pad tissue. CONCLUSIONS: NCI-CONNECT's commitment to innovative designs can mitigate some of the barriers to access experimental therapy for people with rare CNS tumors. This basket trial will enroll participants with unifying molecular features and potential susceptibility to PLX038 despite different histological diagnoses. Furthermore, incorporation of comprehensive PROs will help identify clinical benefit and tolerability while correlative studies in tumor and other tissues will help identify biomarkers of response or resistance.